A Broad Review of Routing Protocols in Mobile Ad-hoc Networking (Asian Journal of Applied Sciences, 2017)
MANET (Mobile Adhoc-Network), is a self-configured wireless infrastructure-less network. Different traditional mobile wireless networks, ad-hoc networks do not depend on any permanent infrastructure. As an,option hosts rely on each other to keep the network connected. It represents intricate distributed systems that include wireless mobile nodes that can freely and dynamically Self-organize addicted to arbitrary and temporary, ‘‘ad-hoc’’ network topologies. This paper attempts to provide a complete overview of this routing protocol in MANET. It first explains the vital role that mobile ad hoc networks took part in the evolution of future wireless technologies and then it reviews the latest research activities in the areas of mobile ad-hoc network applications.